Extent of awareness, knowledge and adoption of different farm machinery by the groundnut farmers in Chittoor district of Andhra Pradesh: EXTENT OF AWARENESS, KNOWLEDGE AND ADOPTION OF DIFFERENT FARM MACHINERY - C HRUDAY RANJAN,; P V SATYA GOPAL,; V SAILAJA,; S V PRASAD, (Journal of Oilseeds Research, 2014)
Andhra Pradesh shares about one-third of groundnut area of the country and occupies third place in production contributing 18.8% of production in the country. In Andhra Pradesh, Chittoor district ranks second in the area and production under groundnut. Keeping this in consideration present study was conducted among groundnut farmers with a view to study extent of awareness, knowledge and adoption of different farm machinery used in groundnut cultivation in Chittoor district of Andhra Pradesh with a sample of 120 farmers. Results unveiled that nearly half of the groundnut farmers were having medium extent of awareness, slightly more than half of the farmers having medium extent of knowledge and with respect to extent of adoption nearly forty three per cent of the farmers were having medium level of adoption. Depending upon the extent of awareness, knowledge and adoption of different farm machinery used by the groundnut farmers were ranked in terms of their awareness, knowledge and adoption.